Beziehungen zwischen Tourismus, ländlichem Kunsthandwerk und Agrarstruktur in einigen Dörfern Zentralmexikos - Sander, Hans-Jörg (ERDKUNDE, 1981)
The sums that the state of Mexico receives from international tourism for the improvement of its balance of payments are rising every year. The planned promotion of tourism in Mexico is discernible, among other things, in the revival and expansion of the many traditional skilled crafts of the country. At the same time this policy pursues the structural aim of increasing the rural carrying capacity by creating extra agrarian forms of employment, and to protect people from migration to the towns. This study draws of the example of three villages in the Central Mexican Highland, each of which specialized either in pottery or the carving of onyx and marble souvenirs or the production of palm-leaf mats and plaitings, discusses some aspects of relations between tourism-related skilled rural crafts and the agrarian structure. The discussion centres on the question of whether and in how far skilled crafts are a suitable means for the long-term increase in rural carrying capacity without becoming detrimental to the agrarian potential. The limits of a development that alters the structure in this way are seen in the threatening - and in some places already spreading - signs of neglect in agriculture. Further evaluation criteria in the treatment of this question are the susceptibility to crises and the dependence on market trends or the tourist-orientated as well as other rural non-agricultural forms of employment, and even the now already widely spread dependence of skilled craftsmen on intermediaries and buyers, together with the trend towards forming rural handicraft cartels.